Knowledge of Primiparous Mothers on Immunization of Children under three Years in Rawalakot, Azad Kashmir: Primiparous Mothers’ Knowledge on Immunization - Iltaf, Shugafta; Khadim, Rehana; Parveen, Shagufta; Shabnum, Nadia (Pakistan Journal of Health Sciences, 2024)
Immunization was crucial aspect of preventing infectious diseases in early childhood. However, lack of knowledge among parents especially primiparous mothers, can hinder optimal immunization coverage. Objective: To assess and evaluate the knowledge level of primiparous mother regarding immunization and the factor influencing immunization status in children under three years. Methods: A cross-sectional study was conducted with a sample of 210 mothers at Combined Military Hospital, Rawalakot, Azad Kashmir, from April 2023 to February 2024, using consecutive sampling. Data were collected using an adapted questionnaire, which included a demographic section and 37 knowledge items. Analysis was done by using SPSS version 26.0, using descriptive statistics (frequency and percentage) and inferential statistics (Chi-Square test). Results: There was gap in literature about primiparous mothers’ knowledge and this study results showed that 27.6% had low, 50% had moderate, and 22.4% had high knowledge. Complete immunization was achieved for 60.5% of children, highlighting the need for improved awareness, especially among primiparous mothers. Higher education and employment were significantly linked to better knowledge (P < 0.001), with healthcare professionals being the main source (56.6%). The study provided crucial insights for the Ministry of Health and policymakers, demonstrating the need to enhance immunization campaigns by improving primiparous mothers’ knowledge for better vaccine coverage. Conclusions: A significant portion of primiparous mothers had moderate to low knowledge about child immunization, contributing to incomplete vaccination rates. Enhanced education and awareness programs, particularly for less informed mothers, were essential to improve immunization coverage in Azad Kashmir.